2020
DOI: 10.1002/cbdv.201900661
|View full text |Cite
|
Sign up to set email alerts
|

Shorea roxburghii Leaf Extract Ameliorates Hyperglycemia Induced Abnormalities in High Fat/Fructose and Streptozotocin Induced Diabetic Rats

Abstract: This study investigated the hypoglycemic effect of the methanol extract of Shorea roxburghii leaves (SRL) in high fat diet/high fructose solution (HFDHF) and streptozotocin (STZ) induced type 2 diabetes mellitus (T2DM) in rats as well as evaluating its ameliorative potentials in altered biochemical and hematological parameters in the treated rats. T2DM was induced in Sprague Dawley (SD) rats by feeding with HFDHF for 4 weeks and administering STZ (35 mg/kg, i. p.). Diabetic rats were given SRL extract at doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The selection of the doses of SRE used in this study was based on previous study 20 . The treatment started immediately after the confirmation of diabetes by oral gavage and lasted for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of the doses of SRE used in this study was based on previous study 20 . The treatment started immediately after the confirmation of diabetes by oral gavage and lasted for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous reports, polyphenolic compounds, particularly stilbenoids and dihydroisocoumarins are the principal bioactive constituents present in S roxburghii 23 . Our previous study indicated that the stilbenoids rich extract (Figure 1) from the leaves of S roxburghii attenuated hyperglycemia induced biochemical and hematological alterations in diabetic rats 20 . However, there are no reports on the ameliorative effect of S roxburghii on diabetes induced testicular damage.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Existing literatures have suggested that natural products especially medicinal plants and their constituent compounds have the ability to protect against multiple organ toxicities induced by CYP [13,14] . Shorea roxburghii is a Dipterocarpaceae tree that is rich in polyphenolic compounds, especially stilbenoids and dihydroisocoumarins [15] . Previous studies have shown that the extract from the leaves and stem back showed ameliorative and protective effects against diabetes induced testicular damage and d‐galactosamine/lipopolysaccharide‐induced liver injury, respectively [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…33 Thereafter, the rats in the experimental group were administered STZ (35 mg/kg, dissolved in freshly prepared citrate buffer; pH 4.5) via intraperitoneal injection to induce diabetes. 34,35 The rats were confirmed diabetic after 3 days of injection by measuring the FBG in overnight fasted rats. Rats with FBG above 250 mg/dL were taken as diabetic and further divided into 2 groups with six rats in each group: the DCG and diabetic rat treated with DHA at a dose of 25 mg/kg (D + DHA).…”
Section: Experimental Animalsmentioning
confidence: 99%